Does hope buffer the impacts of stress and exhaustion on frontline hotel employees'turnover intentions? - Yavas, Ugur; Karatepe, Osman M.; Babakus, Emin (Institute for Tourism tourism@iztzg.hr, 2013)
This study investigates the effects of challenge and hindrance stressors and exhaustion on frontline hotel employees'turnover intentions and whether hope, as a personal resource, can moderate the deleterious effects of these antecedents on turnover intentions. Data were collected from a sample of 183 full-time frontline employees working in 5-star and 4-star hotels in Northern Cyprus. To ensure the temporal separation of measures, data pertaining to the independent and dependent variables were measured via two questionnaires administered with a time lag of two weeks. Results of the study reveal that hindrance stressors and exhaustion heighten frontline employees' turnover intentions and that hope is a potential antidote to the deleterious impacts of these antecedents on turnover intentions. Thus, managers should consider the candidates' hope levels during employee selection and hiring. Candidates high in hope should he given priority in hiring since such employees can better cope with stress and exhaustion. Management should also consider devising proactive strategies to keep employees high in hope in the organization since such employees can help create a positive work environment, may serve as role models to their colleagues and generate a demonstration effect among current employees with lower levels of hope.
Keywords: Exhaustion; Hope; Hotel employees; Northern Cyprus; Stress; Turnover intentions